(untitled) - Fox, Stuart Ira (New York, 2013)
Includes glossary and index; The study of body function -- Chemical composition of the body -- Cell structure and genetic control -- Enzymes and energy -- Cell respiration and metabolism -- Interactions between cells and the extracellular environment -- The nervous system : neurons and synapses -- The central nervous system -- The autonomic nervous system -- Sensory physiology -- Endocrine glands : secretion and action of hormones -- Muscle : mechanisms of contraction and neural control -- Blood, heart, and circulation -- Cardiac output, blood flow, andb lood pressure -- The immune system -- Respiratory physiology -- Physiology of the kidneys -- The digestive system -- Regulation of metabolism -- Reproduction
Keywords: Human physiology; Physiology; Sinh lý học người; Sinh lý học